Pode a Cidadania participativa gerar equilíbrio entre a Política e a Justiça? O caso de Angola - Almeida, E. C. (III Conferência Internacional de Angolanística (painel de trabalho: «A política e o direito, a cidadania participativa»), 2023)
If Politics comes from the Greek “polis” – city-state – and aims at the “conquest, possession and exercise of power” (Rogeiro, 1993: 19-25) taking into account the “art of [well] governing” and that Justice, according to Ulpianus, is “constans et perpetua vuluntas ius suum quique tribuere (i.e., constant and perpetual will to give to each one what is his or her due)” (Ferro, 2021: 21), so it must place The question arises whether Politics and Justice (or Law) can coexist without interfering? And what will be the role of Citizenship within and amidst this sometimes titanic struggle for prevalence? What makes Justice Policy different and how can they – should they – coexist based on an impartial, equitable and balanced Rule of Law? Not forgetting that there is no Citizenship without social rights and that these are obtained through fair policies and that to obtain them it is necessary to have a fair and stable Rule of Law, this is where Citizens can intervene by seeking to understand how they can help to generate this balance through their active, constant and, whenever possible, properly balanced connection so that Justice prevails within the criteria that guide Politics: that is, so that there is a participatory and stable Democracy, a balanced Public Res. In Angola, Citizenship has been showing that it is increasingly active and participatory in political issues and in the search for community justice. Will Citizenship have the capacity to do this? This is what they will try to show and, if necessary, demonstrate their ability.